Conditioned stimulus effects on paired or alternative reinforcement depend on presentation duration: Implications for conceptualizations of craving - Ginsburg, Brett C.; Nawrocik-Madrid, Acacia; Schindler, Charles W.; Lamb, R. J. (Frontiers in Behavioral Neuroscience, 2022)
Conditioned stimuli (CS) associated with alcohol ingestion are thought to play a role in relapse by producing a craving that in turn increases motivation to drink which increases ethanol-seeking and disrupts other ongoing behavior. Alternatively, such CS may provide information indicating a likely increase in the density of the paired unconditioned stimulus and simultaneously elicit behavior that may be incompatible with other ongoing behavior, i.e., approach toward the CS. To explore these possibilities, rats were trained to respond for ethanol or food in two different components of the same session after which a light above the ethanol-lever was lighted twice during each component and each light presentation was followed by ethanol delivery. The duration of this CS was 10 s initially and then increased to 30 s, then to 100 s, and finally returned to 30 s. The change in responding for ethanol or food was compared to a matched period immediately preceding CS presentation. The CS presentation increased responding to ethanol, and this effect increases with longer CS presentations. In contrast, the CS presentation decreased responding to food, and this effect decreases with longer CS presentations. These results appear to support the informational account of CS action rather than simply a change in the motivation to seek and consume ethanol. This suggests that craving as it is commonly understood likely represents multiple behavioral processes, not simply increased desire for alcohol and that reports of craving likely reflect labeling based upon past experiences rather than a cause of future drug-taking.